Border Governance in Kachin State, Myanmar: Un/caring states and aspirant state building during humanitarian crises. (3rd March 2022) - HO, ELAINE LYNN-EE
Abstract: Since 2011 renewed fighting between the Myanmar military and the Kachin Independence Army (KIA) has triggered the internal displacement of more than 100, 000 people in Kachin state. This article examines how care practices and care ethics influence border governance in the context of humanitarian concerns in Kachin state in northern Myanmar, which shares a border with China. The situation in Kachin state at the China-Myanmar border reveals the contrasting territorial logics at stake, the contingency of governance at a time of political transition, and distinct 'regimes of care', as manifested through humanitarian relief, which all contribute towards border governance. Drawing on ethnographic research and interviews, the article highlights how care deficits are met by a separatist government, community organizations (both faith-based and secular), and diaspora populations which mobilize a range of networks and resources—forming webs of connections and interfacing with one another—to provide humanitarian relief. However, their actions and the ensuing flows of care could produce or deepen political subjectivities that are geared towards territorial contestation and separatism, thus changing expressions of border governance. The article further observes that the Kachin situation has wider implications for the peace negotiations taking place at the national level in Myanmar.